Characterization of AHL-type quorum sensing in Cedecea neteri SSMD04 / Tan Kian Hin - Tan, Kian Hin (2018)
Bacteria demonstrate a form of cell-to-cell signalling for the regulation of their gene expression according to the change of population density. This is called quorum sensing. Different bacterial species utilizes different signalling molecules for quorum sensing and the most well studied quorum sensing system is the N-acyl homoserine lactone type quorum sensing found commonly in Gram-negative Proteobacteria. Cedecea neteri is an uncommonly studied bacteria in the Enterobacteriaceae family. It is a known human pathogen with unknown etiology. In a previous study to investigate the presence of bacteria that exhibit N-acyl homoserine lactone type quorum sensing isolated from food sources, a strain of C. neteri SSMD04 was found to exhibit quorum sensing activity, which was the first in this genus. By using triple quadrupole liquid chromatography mass spectrometry, it was identified that C. neteri SSMD04 produces C4-HSL as its signalling molecule. The gene responsible for C4-HSL production and the gene for the receptor that binds to C4-HSL, named cneI and cneR, were later found from its genome. These genes were found to be most closely related to a new species in the Klebsiella genus, Klebsiella michiganensis. However, K. michiganensis has never been reported to exhibit quorum sensing activity. A quorum sensing deficient mutant of C. neteri SSMD04 was later created by λ Red recombineering. Through global comparative transcriptomics, it was shown that N-acyl homoserine lactone type quorum sensing is responsible for the modulation of its metabolism.